CONCEPTS OF GEOECOLOGICAL PROBLEMS AND THEIR SOLUTIONS (using the example of the Fergana Valley) (Scientific journal of the Fergana State University, 2024)
The article describes complex natural-geographical studies conducted in the Fergana Valley in the first half of the last century, geo-ecological problems that emerged after the third quarter of the last century, and concepts for solving them based on them.